(untitled) (International Journal of Environmental Sciences, 2025)
Environmental degradation, climate change, and pollution have escalated the need for efficient monitoring solutions. The integration of the Internet of Things (IoT) into environmental monitoring systems has transformed how data is collected, analyzed, and acted upon in real-time. This review explores the recent trends in IoT-enabled environmental monitoring, examining sensor technologies, cloud integration, edge computing, and machine learning. It also identifies key challenges such as energy consumption, data security, network scalability, and interoperability. Finally, the article discusses emerging directions in the field, including smart city integration, AI-powered predictive analytics, and low-power wide-area networks (LPWANs). This review highlights how IoT-driven innovations offer a promising future for sustainable environmental stewardship and proactive ecological management.